Onsite power system reliability assessment for nuclear power plants - M. Agwa, A.; M. Hassan, H.; E. Matter, Z.; A. Eisawy, E. (International Journal of Engineering and Technology, 2019)
The onsite power system of the Nuclear Power Plants (NPPs) provides electrical energy necessary to bring the plant to a controlled state following anticipated operational occurrences or accident conditions and to maintain it in a controlled state, or a safe state. The onsite power system reliability is essential for reliable and safe operation of the NPPs. The onsite power system reliability for Advanced Power Reactor (APR1400), European pressurized water reactor (EPR) and Advanced Passive (AP1000) are assessed using Fault Tree (FT) analysis technique. The reliability of the onsite power system is evaluated based on the unreliability of the power supplied to safety buses. The overall onsite power systems reliabilities for each design are assessed and compared to each other. Components importance measures are calculated for each plant to identify the most important electrical components in the power system from the nuclear safety point of view.Â Â